The Shelter Concert Series: Reflections on homelessness and service learning. Issue 3 (1st December 2013) - Knapp, David
The Shelter Concert Series was a service-learning project conducted in coordination with a university-music programme and a shelter for individuals experiencing homelessness. Students performed weekly concerts, including a jazz band, steel band, clarinet duet, old time ensemble, acoustic guitarist, rhythm and blues band and a classical vocalist. This article offers a reflective account of practice based on qualitative research. Questionnaire, interview and observation data indicated Shelter clients enjoyed the concerts and were appreciative of the students' performances. Students reported an increase in positive attitudes towards individuals experiencing homelessness, and a desire to participate more often in service learning. Shelter staff believed the concerts led to a more positive atmosphere for the clients. Implications for service learning and music education, especially with individuals experiencing homelessness, are discussed.